CO preferential oxidation on cordierite monoliths coated with CuO-CeO2/SBA-15 catalysts. Further insights into the physico-chemical aspects of the catalytic behavior - Lacoste, Albano Mauricio (2018)
CuO-CeO2/SBA-15 catalysts deposited over cordierite monoliths were prepared to be tested in CO preferential oxidation (COPrOx). The influence of molar ratio between the CuO and CeO2 active phases, their concentration, and the incorporation method into the mesoporous structure were analyzed. Powder catalysts were also studied in order to select the best formulations to coat the monolith walls. Four CuO/CeO2 molar ratios over SBA-15 were obtained by incipient wetness impregnation technique (successive impregnation and co-impregnation). The CuO/CeO2 = 0.55 ratio powder catalyst showed the best CO conversion in the temperature range studied, reaching 100% at 160 °C. The incorporation of active phases into the structured support produced similar or better catalytic behaviors. The addition of 10% CO2 slightly decreased the CO conversion, while the addition of 10% H2O partially deactivated the catalyst. The structured and powder catalysts prepared were characterized by N2 sorption, TEM, SEM, XRD, XPS and TPR in order to identify and relate their physico-chemical properties with the catalytic behavior.